Evaluation of prevalence, biochemical profile, and drugs associated with chronic kidney disease-mineral and bone disorder in 11 dialysis centers - Rodrigo Reis Abrita; Beatriz dos Santos Pereira; Neimar da Silva Fernandes; Renata Abrita; Rosalia Maria Nunes Henriques Huaira; Marcus Gomes Bastos; Natália Maria da Silva Fernandes (Brazilian Journal of Nephrology, 2018)
ABSTRACT Introduction: The diagnosis and treatment of mineral and bone disorder of chronic kidney disease (CKD-MBD) is a challenge for nephrologists and health managers. The aim of this study was to evaluate the prevalence, biochemical profile, and drugs associated with CKD-MBD. Methods: Cross-sectional study between July and November 2013, with 1134 patients on dialysis. Sociodemographic, clinical, and laboratory data were compared between groups based on levels of intact parathyroid hormone (iPTH) (< 150, 150-300, 301-600, 601-1000, and > 1001 pg/mL). Results: The mean age was 57.3 ± 14.4 years. The prevalence of iPTH < 150 pg/mL was 23.4% and iPTH > 601 pg/mL was 27.1%. The comparison between the groups showed that the level of iPTH decreased with increasing age. Diabetic patients had a higher prevalence of iPTH < 150 pg/mL (27.6%). Hyperphosphatemia (> 5.5 mg/dL) was observed in 35.8%. Calcium carbonate was used by 50.5%, sevelamer by 14.7%, 40% of patients had used some form of vitamin D and 3.5% used cinacalcet. Linear regression analysis showed a significant negative association between iPTH, age, and diabetes mellitus and a significant positive association between iPTH and dialysis time. Conclusion: The prevalence of patients outside the target for iPTH was 50.5%. There was a high prevalence of hyperphosphatemia (35.8%), and the minority of patients were using active vitamin D, vitamin D analogs, selective vitamin D receptor activators, and cinacalcet. These data indicate the need for better compliance with clinical guidelines and public policies on the supply of drugs associated with CKD-MBD.